STRATEGI KESANTUNAN POSITIF DALAM SURAT-MENYURAT BISNIS: ANALISIS PRAGMATIK TERHADAP SURAT-SURAT DALAM OXFORD HANDBOOK - Afriana, Afriana; Hanus Tewarat, Sipri; Arianto, Tomi; Lismalinda, Lismalinda (Asosiasi Ide Bahasa Kepri, 2025)
This study investigates the application of positive politeness strategies in formal business correspondence written by native English speakers. The research is motivated by the increasing recognition of politeness as a pragmatic tool in maintaining professionalism and managing interpersonal relationships in written communication. Despite numerous studies on digital communication, there is limited analysis of how politeness strategies are systematically employed in conventional business letters. To address this gap, the study analyzes fifteen letters selected from the Oxford Handbook of Commercial Correspondence. Using Brown and Levinson’s (1987) politeness theory and Nickerson’s (1999) typology of business letter components, the research focuses on elements such as salutations, contexts, pre-closes, closings, signatures, and enclosures. A qualitative descriptive approach was used, with the referential identity technique applied to classify and interpret 121 instances of politeness strategies. The results show that the most frequent strategy was the use of appropriate forms of address (45 instances), followed by establishing common ground, expressing optimism, and asserting knowledge. These strategies appeared consistently across letter components, reflecting their dual function as both communicative and relational tools. The findings highlight the central role of linguistic politeness in reinforcing professionalism, fostering mutual respect, and encouraging future cooperation. This study concludes that positive politeness is not merely ornamental, but a vital rhetorical device in written business interaction. Future research may explore how these strategies vary across cultural contexts or adapt in digital business communications.